Digital Transformation in HR Management: The Impact of Automation on Employee Productivity and Wellbeing - Farawowan, Fauziah F.; Rosalia, Olyvia; Firayani, Firayani; Prasetyo, Andreas Recki (Pt. Anagata Sembagi Education, 2025)
Digital transformation in Human Resource Management (HRM) has become a major focus for many organizations to improve operational efficiency and effectiveness. One of the most prominent aspects is the implementation of automation in various HR processes, from recruitment, training, to performance appraisal. This study aims to analyze the effect of automation on the productivity and well-being of employees in the organization. By using quantitative methods through surveys to employees in several companies, the results showed that the implementation of automation in the HR sector can increase work productivity, reduce administrative burden, and provide more time for employees to focus on more strategic tasks. In addition, automation enables organizations to take more accurate, data-driven decisions, thereby increasing the effectiveness of HR strategies. However, automation also poses new challenges, including anxiety related to work roles, adaptation to technology, and employee mental well-being. Lack of training and effective communication can trigger resistance from employees to the changes taking place. Therefore, it is important for organizations to consider a balanced approach between technology and human aspects in the implementation of automation in HR management, including communication strategies and employee skill development so that the digital transition can run smoothly and sustainably.